Fears of Children at Pre-school Age in the Formation of the Image of the World - Romenkova, Valentīna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
There are many studies dedicated to children’s fear. Fear is an integral part of a man’s emotional life. Fear – a condition of great agitation, restlessness, alarm of the mind in situation of menacing danger or calamity, affectively acute perception of threats for one’s life, feeling and well-being. Fear can be described both as normative that helps to mobilize in a dangerous situation, and as destructive. The focus of this study was to determine the place and role of fear in shaping the Image of the World of a child at pre-school age. The author was interested in how fear, a negatively colored emotional phenomenon, embedded or integrated itself into the structure of the world image of a child, who normally is happy and optimistic. The hypothesis of the study was as follows: if the phenomena generating fear that goes beyond the experience of children are explained by adults, the children can overcome it easy, and the verbal characteristics of the phenomenon are in tune with the general upbeat tone of the Image of the World.